Sosialisasi Psikoedukasi sebagai Intervensi Dini dalam Pengelolaan Emosi Remaja - Hanifah Hanifah; Olivia Ayuningrum; Tri Widya Nengsih (SIGMA : Jurnal Sinergi Mengabdi, 2025)
The extent to which adolescents are able to recognize and understand their emotions determines their ability to manage emotions. This community service discusses the socialization of psychoeducation as an early intervention in adolescent emotion management. Adolescents in orphanages who have not been able to recognize the various emotions they have need attention, because this can affect the way they manage emotions, thus having a negative impact on the learning process. Therefore, this service program is focused on psychoeducation related to the recognition of emotions, the function of emotions, the kinds of emotions, the application of emotions, and how to manage emotions, and express emotions properly. The method used includes the PAR (Participatory Action Research) method by involving active participation from the community or research subjects in every stage, from problem identification to implementation and evaluation. The results of the community service showed that the psychoeducational socialization activities related to adolescent emotional management consisted of a pre-test, two sessions of material (i.e., session 1 on the socialization of the seminar on self-awareness of emotions, and session 2 on the delivery of material on how to manage emotions and express emotions appropriately), and concluded with a post-test related to emotional management. In addition, there was a significant increase in understanding of emotions and how to manage them. The psychoeducational socialization activities helped adolescents in the orphanage to better recognize their feelings and learn how to express them appropriately. This program contributes to shaping the next generation of a superior and noble nation. Psychoeducation can also be an initial solution for adolescent emotion management and can be applied in other orphanages.